(untitled) (American Journal of Technology and Applied Sciences, 2026)
The paper investigates the formation processes, structural features and morphology of thin films of manganese silicides obtained by ion implantation of manganese into single-crystal silicon followed by thermal annealing. It has been shown that at low implantation doses and annealing temperatures up to 600 °C, silicidal phases are predominantly in an amorphous or nanocrystalline state. Increasing the implantation dose to and the annealing temperature to 700–800 °C results in the formation of crystalline phases of MnSi and Mn₅Si₃. The size of crystallites, estimated from X-ray diffraction analysis, increases from 20–30 nm to 50–60 nm with increasing annealing temperature.10^16 〖см〗^(-2) Atomic force microscopy has established that an increase in the degree of crystallinity is accompanied by a change in the morphology of the surface: the RMS roughness increases from 0.8 nm at 600 °C to 4–5 nm at 800 °C, while a granular and insular structure is formed. Measurements of the electrical properties showed a decrease in the resistivity of the films to values of the order of Ω10^(-4)⋅cm under optimal annealing regimes, which correlates with an improvement in the crystal order.